Single molecule measurements of titin elasticity - Wang, Kuan; Forbes, Jeffrey G.; Jin, Albert J. (Progress in Biophysics and Molecular Biology, 2001)
Titin, with a massive single chain of 3–4 MDa and multiple modular motifs, spans the half-sarcomere of skeletal and cardiac muscles and serves important, multifaceted functions. In recent years, titin has become a favored subject of single molecule observations by atomic force microscopy (AFM) and laser optical trap (LOT). Here we review these single titin molecule extension studies with an emphasis on understanding their relevance to titin elasticity in muscle function. Some fundamental aspects of the methods for single titin molecule investigations, including the application of dynamic force, the elasticity models for filamentous titin motifs, the technical foundations and calibrations of AFM and LOT, and titin sample preparations are provided. A chronological review of major publications on recent single titin extension observations is presented. This is followed by summary evaluations of titin domain folding/unfolding results and of elastic properties of filamentous titin motifs. Implications of these single titin measurements for muscle physiology/pathology are discussed and forthcoming advances in single titin studies are anticipated.